The economic, social and environmental implications of heritage tourism: Evidence from Bangladesh - Islam, Md. Karimul; Farjana, Fariha; Nasrin, Nishad; Ahmed, Md. Shakil (Springer Link, 2024)
This article was published in The SN Business & Economics [©2023 Rights managed by Springer Link] and the definite version is available at: https://doi.org/10.1007/s43546-022-00411-2 The Article's website is at: https://link.springer.com/article/10.1007/s43546-022-00411-2